The effect of mineral fertilizers on productivity of the new spring barley variety ‘Znatny’ in the non-blackearth part of the Russian Federation - О. V. Levakova; O. V. Gladysheva (Зерновое хозяйство России, 2021)
An increase in spring barley acreage requires a detailed study of the interaction of agronomic and climatic factors, as well as the selection of a modern set of new varieties. The use of mineral fertilizers is one of the most important methods to improve the productivity of grain crops and maintain a deficit-free balance of mineral nutrients in arable soils. The current study of the effective use of various doses of mineral fertilizers (NPK) on the new spring barley variety ‘Znatny’ was carried out on dark-gray forest heavy loamy soil in 2018–2020 by the Institute of Seed production and Agrotechnologies, a branch of the Federal Budgetary Scientific Institution “Federal Research Agro-Engineering Center VIM”. There has been established that the date of the phenological phases and the length of interphase periods did not depend on fertilizer rates, but had a close correlation with weather conditions (r = +0.68). The analysis of the obtained data has shown that an increase in the rates of applied fertilizers increases the aboveground biomass, which, in turn, negatively affects productivity of the barley variety ‘Znatny’ (r = -0.77). The analysis of the yield structure and rates of fertilizers NPK has shown that in the trial, the spring barley productivity was influenced by 1000-grain weight (r = +0.60). There was found a high inverse correlation between productivity and length of head (r = -0.85). When length of head ranged from 7.5 to 8.4 cm, grain weight per head remained practically at the same level in all variants (1.1–1.2). This indicated that at a rate of N90P90K90 and N120P120K120, the variety ‘Znatny’ formed a not very dense head. Protein percentage at these rates also greatly reduced. According to the obtained data, an increase in the doses of applied fertilizers (N90Р90К90–N120Р120К120) resulted in the intensified development of most leaf diseases and a decrease in lodging resistance. Thus, the optimal dose of application of azophoska fertilizer on dark-gray forest soil is the norm N45P45K45, since on this option there was obtained maximum productivity and net income. the increase in the recom[1]mended norms of mineral fertilizers, sharply reduces profitability of crop cultivation.